Characterization of feline cytochrome P450 2B6. (1st February 2017) - Okamatsu, Gaku; Komatsu, Tetsuya; Ono, Yuka; Inoue, Hiroki; Uchide, Tsuyoshi; Onaga, Takenori; Endoh, Daiji; Kitazawa, Takio; Hiraga, Takeo; Uno, Yasuhiro; Teraoka, Hiroki
Abstract: 1. Little is known about drug metabolism in carnivores. Although the domestic cat ( Felis catus ) is an obligate carnivore and is the most common companion animal, usage and dosage of many drugs are determined according to information obtained from humans and dogs. We determined the complete cDNA sequence of CYP2B6 from the feline lung. 2. Feline CYP2B6 consists of 494 deduced amino acids, showing highest identity with the dog CYP2B ortholog, followed by those of horse, pig, primate and human. 3. Feline CYP2B6 transcripts were expressed predominantly in the lung and slightly in the small intestine but not in the liver without significant sex-dependent differences. Western blot analysis with an anti-human CYP2B6 antibody confirmed the presence of CYP2B protein in the lung but not in the liver. 4. Feline CYP2B6 proteins heterologously expressed in Escherichia coli metabolized several substrates specific to human CYP2B6, including 7-ethoxy-4-(trifluoromethyl) coumarin (EFC). The metabolic activity was strongly inhibited by medetomidine and atipamezole, potent inhibitors of canine CYP2B11 (now officially CYP2B6) as well as by ticlopidine and sertraline, inhibitors selective to human CYP2B6. 5. The results suggest that feline CYP2B6 is a functional CYP2B ortholog that plays a role in the local defense mechanism in the cat respiratory system and intestine.